13x + 2y = 1
5x - 2y = -19
Use the substitution method to solve this system of equations. In the first equation, solve for y.
13x + 2y = 1
Subtract 13x from both sides.
2y = 1 - 13x
Divide both sides by 2.
y =
![(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/q5zg49mbtfrwobmmahi676fbgez56hhab0.png)
-
![(13)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/i02pqm1wc8owukqy6lc3ld98eg3livuzkl.png)
x
Now plug y into the second equation.
5x - 2(
![(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/q5zg49mbtfrwobmmahi676fbgez56hhab0.png)
-
![(13)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/i02pqm1wc8owukqy6lc3ld98eg3livuzkl.png)
x) = -19
Distribute -2 to
![(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/q5zg49mbtfrwobmmahi676fbgez56hhab0.png)
-
![(13)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/i02pqm1wc8owukqy6lc3ld98eg3livuzkl.png)
x.
5x - 1 + 13x = -19
Combine like terms.
18x - 1 = -19
Add 1 to both sides.
18x = -18
Divide both sides by 18.
x = -1
Now plug x back into the "new" first equation (where we solved for y).
y =
![(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/q5zg49mbtfrwobmmahi676fbgez56hhab0.png)
-
![(13)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/i02pqm1wc8owukqy6lc3ld98eg3livuzkl.png)
(-1)
Multiply
![(13)/(2)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/i02pqm1wc8owukqy6lc3ld98eg3livuzkl.png)
by -1.
y =
![(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/q5zg49mbtfrwobmmahi676fbgez56hhab0.png)
+ 6
![(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/q5zg49mbtfrwobmmahi676fbgez56hhab0.png)
= 7
y = 7
x = -1, y = 7